Pengaruh Penggunaan Video Animasi Terhadap Minat Belajar Siswa Pada Tema Organ Gerakan Hewan Di Kelas V Sekolah Dasar - Riana Aprianti Riana Aprianti; Cece Rakhmat; Dian Indihadi (Elementary Teacher Education Program, Majalengka University, 2023)
Student involvement and participation in the learning process has not shown student activity. Students tend to be less enthusiastic and proactive in participating in learning. This study aims to determine the effect of animated videos on increasing interest in learning and student perceptions. This type of research is experimental research with a research design using a non-equivalent control group design. The subjects of this study were fifth grade elementary school students as the population and sample. The sampling technique used purposive sampling. The research instrument used test and lift. The data analysis used was hypothesis testing on students' interests and perceptions. The results showed that there was no difference between the students' initial abilities before the application of animated video media between the experimental and control classes. Meanwhile, the final ability and interest in student learning after the application of animated video media experienced a significant difference. Perceptions of experimental class students towards animated video media showed a very good attitude. It can be concluded that animated videos are proven to have a significant influence on students' interests and perceptions